Artificial intelligence and innovation practices: A conceptual inquiry - Boyke Rudy Purnomo (Universitas Ahmad Dahlan, 2023)
Discourse on artificial intelligence runs noticeably along with the developments of computing technology. At the same time, the business environment become more uncertain, ambiguous, and competitive, which requires organizations to innovate for their sustainability continuously. This paper aims to broaden the body of knowledge on innovation management, particularly in relation to the application of artificial intelligence. The behavioural Theory of the Firm is used as a framework for writing this conceptual inquiry. To do so, artificial intelligence can assist organizations in processing information needed by companies to create incremental and radical innovations. Specifically, artificial intelligence is useful in overcoming barriers to innovation (during information processing and search processes) and in the process of generating and developing ideas and solutions. Furthermore, the process of adopting artificial intelligence in innovation management areas is determined by the level of organizational capability in information processing, which consists of three levels, namely exploitation, expansion, and exploration. Then, economic, technological and social forces are argued as factors that can push organizations to adopt artificial intelligence. At the same time, the challenges faced in the adoption process can come from technical aspects of technology, individual elements, and characteristics of interaction between technology and humans. The final part of this manuscript describes the future research agenda that can be carried out related to artificial intelligence and innovation management.